Competencies for successful self-regulated learning in higher education: structural model and indications drawn from expert interviews - Dresel, Markus; Schmitz, Bernhard; Schober, Barbara; Spiel, Christiane; Ziegler, Albert; Engelschalk, Tobias; Jöstl, Gregor; Klug, Julia; Roth, Anne; Wimmer, Bastian; Steuer, Gabriele (Studies in Higher Education, 2015)
<!–StartFragment–>A global characteristic of higher education is the opportunity and necessity for students to self-regulate their learning. In contrast to considerable research focusing on self-regulated learning (SRL) from a behavioural perspective, little is known concerning the underlying competencies which enable students to succeed in SRL. A structural model is proposed that differentiates SRL competencies in terms of descriptive, procedural, and conditional knowledge regarding different types of self-regulation strategies in different phases of the learning process. Indications drawn from semi-structured interviews with N = 108 experts (39 lecturers and 69 as excellent nominated students) from 4 fields of study are in line with core assumptions of the proposed model. Moreover, the results provide a basis to ensure the content validity of assessments of students' SRL competencies and from which to derive standards to judge these competencies.<!–EndFragment–>
Keywords: competencies; expert interviews; learning situations